ACCOUNTING FOR RISKS OF USING SHALLOW GROUND WATER FOR SECONDARY CROPS ON LOWLAND PADDY FIELDS IN INDONESIA - D. Useng (International Association of Lowland Technology, 2013)
Most paddy fields in Indonesia laid on the lowland area and many of them have not sufficient water supply during the dry period. To maximize the use of land, some farmers planted secondary crops using the available shallow water table along the coastal areas. Some common plants planted during dry period on the lowland paddy fields are corn (Zea mais), soybean (Glycine max), groundnut (Arachis hypogaea), chili pepper (Capsicum annum), tomato (Lycopersicum esculentum), and mungbean (Phaselous radiatus). The use of secondary crops on paddy fields using shallow ground water embedded some potential risks that need to be counted. The study conducted to model the risks (production and market risks) associated with the ground water quality and irrigation application methods on the net returns on several crops under different irrigation treatments and application uniformities. Six crops were analyzed to show the potential return under furrow and border irrigation scenarios. Economic reliability measured in terms of Discounted Cash Flow performance of each type of crop. The risk analysis reveals that the three crops means that the crops are less risky than to the other three. The model sensitivity analysis performed to show the influence of input variables to the model outputs and the result showa the commodity prices inflation and ground water salinity are most sensitive to influence the model output.